Comparison between exfoliative cytology and histopathology in detecting oral squamous cell carcinoma - Magdi Mansour A Salih; Maha Omer Bushra; Abdulla H El Nabi; Nadia Ahmed Yahia (Wolters Kluwer Medknow Publications, 2017)
Objectives: To compare the cytological findings of preoperative buccal smears with their histopathological types in oral cavity tumors. Materials and Methods: This study investigated 45 patients with oral tumors who had undergone preoperative buccal smears of oral lesions and were diagnosed by postoperative histopathological examination. Two samples were taken from patients that were clinically diagnosed with oral squamous cell carcinoma (OSCC): smears for cytological examination and biopsies for histopathological diagnosis. Results: Of the 45 cases studied, histopathology showed the presence of OSCC (n = 39 [86.7%]), verrucous carcinoma (n = 2 [4.4%]), and hyperkeratosis (n = 4 [8.9%]). OSCC cases predominantly occurred in males, with a ratio of 3.8:1 (P = 0.000); the majority of OSCC cases, in both males (27; 87%) and females (6; 75%), were older than 50 years. Most OSCC cases, 32 (82.1%), were toombak dippers, and 28 out of the 32 were males (87.5%). In addition, the labiogingival, a common site of toombak dipping, was a prevalent lesion site of OSCC (13 patients, 33.3%) (P = 0.004). The cytological findings showed good diagnostic concordance with the histopathological findings; in 39 cases of OSCC, 31 patients had positive smears and biopsies and eight patients had negative smears but positive biopsies, for an overall sensitivity of 79.5% and specificity of 100%. Conclusion: Despite the small number of cases in this study, we realized that the diagnostic accuracy of preoperative buccal smear cytology for oral lesions was high and that it is a safe, easy-to-perform, and clinically useful diagnostic procedure.